Supply chain resilience for global operations (2) : a re-evaluation of performance benchmarking - Khoo, Yong Lin (Nanyang Technological University, 2021)
Supply chain comprises a network of key players and drivers facilitating the flow of products and information from the supplier to the end consumer. These drivers include information, transportation and warehousing. Given current global circumstances, such as the Covid-19 pandemic and geopolitical issues, it is evident that the supply chain drivers are always exposed to risks and disruptions. It is extremely important that these drivers remain resilient in the face of such risks to ensure continuous flow of critical products and information. Through the use of various benchmarking frameworks, the performance of these drivers can be consistently monitored, by identifying areas requiring improvement and ensuring they do not fall behind along with changes to the supply chain. However, supply chain disruptions may also result in some metrics in these benchmarking frameworks becoming obsolete, thus, it is crucial that the frameworks are constantly improved and kept relevant, sustainable and effective. Therefore, this report aims to re-evaluate current benchmarking frameworks that are used in one of the key drivers in supply chain – warehousing. Ultimately, this report will provide recommendations on new benchmarking metrics and improvements to be made to the current frameworks. Firstly, research was done on warehousing, to understand the processes within warehousing, and its role in the entire supply chain. Additionally, literature reviews were done to identify commonly used benchmarking frameworks in warehousing, which are then evaluated against three pre-determined measures – relevance, sustainability, effectiveness. To further substantiate the research, interviews with industry professionals are also conducted. Finally, the evaluation of the benchmarks, coupled with gaps that were highlighted, are used to provide recommendations of new and improved metrics.